2002
DOI: 10.1097/00003246-200202000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative power on mortality of a modified Sequential Organ Failure Assessment score for complete automatic computation in an operative intensive care unit

Abstract: Despite a number of differences between completely automated data sampling of SOFA score values and manual evaluation, the technique used in this study seems to be suitable for prognosis of the mortality rate during a patient's stay at an operative ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 10 publications
1
28
0
3
Order By: Relevance
“…The body of research on the attributes of the SOFA score shows that it has good to excellent performance to discriminate the status (dead or alive) at discharge of critically ill patients [3][4][5][6]15,[19][20][21][22][23][24], but despite this large body of evidence, only a handful of studies have formally reported on the validity of the SOFA score by using independent samples to test the accuracy and calibration of their findings [11,12,17,25,26]. By omitting a formal evaluation of the attributes of the score in independent samples, the reported properties of the SOFA score can only be generalized with caution to other groups of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…The body of research on the attributes of the SOFA score shows that it has good to excellent performance to discriminate the status (dead or alive) at discharge of critically ill patients [3][4][5][6]15,[19][20][21][22][23][24], but despite this large body of evidence, only a handful of studies have formally reported on the validity of the SOFA score by using independent samples to test the accuracy and calibration of their findings [11,12,17,25,26]. By omitting a formal evaluation of the attributes of the score in independent samples, the reported properties of the SOFA score can only be generalized with caution to other groups of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, dynamic assessment of the SOFA score is superior at predicting 28-day survival/mortality [39][40][41]. Furthermore, modifications of the SOFA score [42][43][44][45][46] have been shown to have good discrimination of development of more severe morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The SOFA score has been modified previously for surgical 21 and trauma patients 22 , as well as for children 23 In a search for a scoring model for patients with cancer, Groeger et al developed the Intensive Care Unit Cancer Mortality Model 7 , and that score was customized later to be used in patients under mechanical ventilation 25 and to evaluate the outcomes of patients with cancer after 72 hours of intensive care management 26 . The Intensive Care Unit Cancer Mortality Model score performed well, but it is complicated to calculate and not feasible for use in large administrative and clinical data sets.…”
Section: Discussionmentioning
confidence: 99%